Hiding and retrieval of text content using discrete cosine transformation (DCT) and tripledes (3Des) method - Sivasangari, Krishnan (2013)
Computer security features for web applications are widely needed in many fields especially in defense industry. Detection phase is the most important aspect in the security development. Detection and investigation is commonly used to identify the suspected evidences from the computer crime. Steganography technique become the common approach for detect image based evidence. Previously, encryption technique is applied into image which is trial and error is applied to get precise evidences. This will cause the evidence to be not valid if proceed to the court. In this project steganography is used to get precise set of evidences in order to achieve desired proof to proceed to the court. Based on project, steganography is able to produce the output that precise to the desired output. From the output, the text document saved into computer to produce a solid evidence so that the cases related cybercrime can be proceed to the court. This technique overcomes the problem of trial and error in encryption to get the desired evidences. Steganography with encrypted able to produce a strong security environment in the computer to preserve the confidential and private information.